Using language-based search in mining large software repositories - Awang Abu Bakar, Normi Sham (2011)
Language component plays an important role in data/information retrieval. Data retrieval in software engineering is often hindered by the difficulty of getting data from commercial software. The emergence of the open source repositories has contributed tremendously in the collection of software data. This paper highlights the data retrieval method for mining software from a vast open source software repository, SourceForge. For the purpose of automating the data retrieval from the repository, a parser was written using the Python programming language, and based on the pattern matching algorithm. The retrieved data were later used to estimate the quality of the open source software.